БЎЛАЖАК ФИЗИКА ЎҚИТУВЧИЛАРИНИНГ МЕТОДИК ТАЙЁРГАРЛИГИНИ ТАКОМИЛЛАШТИРИШ - Карлыбаева, Г.Е. (SCIENCE and SOCIETY, 2018)
Systemic organisation of the study process in hisher educational institutions – plays greot role in preparing hish qualified competiable specialists in job marketing and it also increases methoddocal competition of the future teachers of physics. This article gives actual issues of organization of excellent study process for achiving hisher results in preparing hisher qualifiol staff.
Keywords: future physics teachers; innovation; competence; educacational-process